Analisis Perdagangan Berjangka Komoditi (Future Trading) Berbasis Resi Gudang - Ananda, Candra Fajri (Jurnal Aplikasi Manajemen, 2009)
Price unstabilty of agricultural products, especially in harvest season tends mostly to reduce farmer welfares. In contrary, during off-season, the agricultural product prices will increase gradually and finally deteriorate the consumer utility. Therefore, post-harvest management is inteded to stabilize market prices through product management (future trading based on inventory management). Moreover, it is also inteded to facilitate credit of business sector by using stock as guarantee. This study is aimed to develop a future trading model of agricultural product in East Java. By using growth ratio, purchasing power index, farmer added value index, Analytical Hierarchy Process (AHP) are found out that this policy should be based on product characteristics, prices, and quantity.